2023
DOI: 10.1097/corr.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Reach of Orthopaedic Research Posted to Preprint Servers: Are We “Undercooking” Our Science?

Abstract: Background Although biomedical preprint servers have grown rapidly over the past several years, the harm to patient health and safety remains a major concern among several scientific communities. Despite previous studies examining the role of preprints during the Coronavirus-19 pandemic, there is limited information characterizing their impact on scientific communication in orthopaedic surgery. Questions/purposes (1) What are the characteristics (subspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Rizk et al [9] examined the risks of preprints in the orthopaedic specialty, which has been generally insulated from the worst effects because of policies put in place years ago by its leading journals. These researchers found that posting of preprints in orthopaedics, while uncommon, has increased, with potentially deleterious effects if the practice is allowed to become commonplace.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Rizk et al [9] examined the risks of preprints in the orthopaedic specialty, which has been generally insulated from the worst effects because of policies put in place years ago by its leading journals. These researchers found that posting of preprints in orthopaedics, while uncommon, has increased, with potentially deleterious effects if the practice is allowed to become commonplace.…”
Section: Where Are We Now?mentioning
confidence: 99%